Konsep Pendidikan: Kajian singkat menurut perspektif Anies Rasyid Baswedan - Gultom, Adelia Angelia; Halimah, Nur; Rantina, Meilanta; Santoso, Gunawan (Jurnal Pendidikan Transformatif, 2023)
The goal of this research is to find out the thoughts and perspectives of Anies Rasyid Baswedan from the SDIT AL MU'MIN TV YouTube channel entitled "The Concept of Education". In this study, the writer used a qualitative descriptive method that observed and recorded because the source of the data was obtained by listening to oral narratives. The results of this study explain that education is a process of habituation. This learning also states that education does not form but grows, which directly encourages changes in a person's abilities, both changes in the quality of cognitive, affective and psychomotor abilities. his life as a person, a professional worker, a citizen and a citizen and a creature of God. Learning begins with the event of organizing accessions in conveying the concept of education. Education is about the future in preparing and growing a new generation. This means that education is an effort to realize teaching and learning activities and the learning process actively to develop their potential.